Influencia de los niños con síndrome de down en el autoestima de los padres en el instituto de niños especiales de El Oro, de la ciudad de Machala, período lectivo 2013-2014. - Anzules Cheverría, Alexis Alexandra (2014)
In reality, the importance of rebuilding the self-esteem of parents of children with special needs is limited, in theory how important it is that parents have a willingness and self-esteem to face this situation and all that entails is known, but in practice it does not contribute to promoting it.